2014
DOI: 10.1073/pnas.1315445111
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide activity of unliganded estrogen receptor-α in breast cancer cells

Abstract: Estrogen receptor-α (ERα) has central role in hormone-dependent breast cancer and its ligand-induced functions have been extensively characterized. However, evidence exists that ERα has functions that are independent of ligands. In the present work, we investigated the binding of ERα to chromatin in the absence of ligands and its functions on gene regulation. We demonstrated that in MCF7 breast cancer cells unliganded ERα binds to more than 4,000 chromatin sites. Unexpectedly, although almost entirely comprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
95
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(108 citation statements)
references
References 39 publications
12
95
1
Order By: Relevance
“…3). A recent study demonstrated a role of AP2g in chromatin binding of unliganded ERa and unliganded ERa-regulating AP2g expression (47). AP2g is also essential for ERa-mediated long-range chromatin interaction (48).…”
Section: Discussionmentioning
confidence: 99%
“…3). A recent study demonstrated a role of AP2g in chromatin binding of unliganded ERa and unliganded ERa-regulating AP2g expression (47). AP2g is also essential for ERa-mediated long-range chromatin interaction (48).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, genes possessing preferential binding sites for SRC3 have predictive value for clinical outcome [79] . Moreover, in MCF7 cells, unliganded ERα binding to many sites in the chromatin is considered to be involved in maintenance of hormone-dependent breast cancer cells [80] .…”
Section: Identification Of Estrogen-responsive Genes Using Highthrougmentioning
confidence: 99%
“…It is also reported that CD200 could be a new prognostic factor in acute myeloid leukaemia (21). ESR1, a ligand-activated transcription factor, involves in pathological processes of breast (22)(23)(24)(25), prostate (26) and non-small cell lung cancer (27).…”
Section: Discussionmentioning
confidence: 99%